Analysis of Public Service Quality: A Case Study of Customers at the Official Yamaha Dealer in Sengkang Wajo Regency - Sitti Aminah; Asmanurhidayani Asmanurhidayani; Riza Ananda (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This study to analyze the quality of public services describe the supporting factors and inhibiting factors of the quality of publik services (Case Study on Customers of the Yamaha Sengkang real Dealer, Wajo Regency). This study employs a desricriptive method with a qualitative approach.Data collection was conducted through observation, in depth interviews, and document analysis. Data analysis employed the interactive model developed by Miles and Huberman, comprising data reduction, data display, and conclution drawing. The research findings indicate that service quality at the Official Yamaha Dealer in Sengkang, Wajo Regency, is generally saticfactory. The tangibels dimension is evidenced by adequate sercice facilities, a comfortable waiting area , and a clean, organized work environment. Regarding the empathydimension, employees demostrate attentiveness to customer needs by providing service that is friendly, communicative, and non discriminatory.Inhibiting factors include service wait times during peakhours, limited stock of certain spare parts, and the need for faster customer complaint resolution,conversely,supporting factors include the high quality of service at the Official Yamaha dealer in Sengkang, Wajo regency, alongside ongoing efforts to improve service timt efficiency, optimize complaint handling systems, enhance human resource competence, and leverage information tecnology to facilitate faster, transparent, and customer sattisfaction-oriented service.